Growth and Development of Tristaniopsis merguensis Seedling Inoculated by Natural Ectomycorrhiza - Triadiati Triadiati; Anastastia Raditya Hidayanti; Nampiah Sukarno (Journal of Tropical Life Science, 2020)
Tristaniopsis merguensis (pelawan tree) is a potential plant, however, it has not cultivated and conserved optimally due to slow growth and lack of information about the cultivation. The existence of T. merguensis in the forest is important because pelawan fungi grow under the tree, particularly in the above of the roots. Information about how to grow the T. merguensis seedling is very limited; therefore, research in growth and development of T. merguensis seedling was important. The aims of this study were to determine the appropriate planting medium for T. merguensis seed germination and to stimulate growth and development of T. merguensis seedling by using its fungi. Status of T. merguensis fungi was studied by analyzing root morphology. Fungi isolation was carried out from colonized root and fungi fruit body. The stimulated the growth of T. merguensis seedling was done by using fungi isolated from colonization root in laboratory scale, as well as treated at a different phosphate concentration. The result showed that T. merguensis was associated with ectomycorrhizal fungi. Planting medium consists of sawdust and T. merguensis fine root resulted the highest percentage of germination. Seedlings were treated with ectomycorrhizal fungi grew better than without ectomycorrhizal fungi. In addition, seedlings treatment with ectomycorrhizal fungi and phosphate 25% showed the highest growth rate.Â